Comparison of hypersensitive plum rootstocks - Hilsendegen, Peter (Acta Agraria Debreceniensis, 2018)
New bred plum rootstocks are compared with ‘Prudom’ as a growing standard. Combined with ‘Cacanska lepotica’ and ‘Jojo’ the rootstocks ‘Prudom’, ‘Dospina 235’ and ‘Docera 6’ were involved in this comparison. Following the first five years, no variant showed inaffinity. The vegetative performance of ‘Prudom’ and ‘Dospina 235’ was in the same range (±5–10%). ‘Docera 6’ shows vigour reduction (12–14%). ‘Prudom’ and ‘Dospina 235’ are also in the same range of generative performance (‘Cacanska lepotica’ -19%, ‘Jojo’ +4%). The cumulated yield in Docera 6’ was more or less half quantity. The results of the first five years are too young for valid practical advice. Furthermore, it opens the perspective for alternative rootstock of prune industry in areas with high virus pressure.